The Sage Handbook of Media and Migration, Kevin Smet, Koen Leurs, Myria Georgiou, Saskia Witteborn and Radhika Gajjala (eds) (2019). (1st June 2020) - Gabor, Elena
The Sage Handbook of Media and Migration, Kevin Smet, Koen Leurs, Myria Georgiou, Saskia Witteborn and Radhika Gajjala (eds) (2019)Thousand Oaks, CA: Sage, 684 pp., ISBN 978-1-52644-721-0, e-book, $93